2023
DOI: 10.3390/vaccines11020440
|View full text |Cite
|
Sign up to set email alerts
|

Differential COVID-19 Vaccination Uptake and Associated Factors among the Slum and Estate Communities in Uganda: A Cross-Sectional Population-Based Survey

Abstract: Vaccination against COVID-19 remains one of the ultimate solutions to the ongoing pandemic. This study examined and compared the completion of primary COVID-19 vaccination series and associated factors in the slum and estate communities of Uganda. This was a cross-sectional survey conducted among 1025 slum and estate residents. Logistic regression models were fitted. Of the 1025 participants, 511 were slum residents and 514 were estate residents. Completion of COVID-19 vaccination was 43.8% in the slum communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 40 publications
0
12
1
Order By: Relevance
“…On further screening, 42 articles remained for eligibility assessment after excluding those which were not original studies and not done in slum/underserved communities. The final assessment yielded 24 articles for further analysis [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On further screening, 42 articles remained for eligibility assessment after excluding those which were not original studies and not done in slum/underserved communities. The final assessment yielded 24 articles for further analysis [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen (17) studies reported on the factors associated with COVID-19 vaccination (acceptance/hesitancy and uptake), Table 5 . Older age was a strong predictor reported in nine studies, with some reporting a positive association with acceptance and uptake [ 28 , 30 , 35 , 38 , 41 , 42 , 47 ] and a negative association in others [ 27 , 29 ]. High education level and good health literacy were also positive correlates of vaccine acceptance and uptake [ 25 , 29 , 37 , 39 , 42 ], though some studies reported a negative association [ 32 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a study done among residents of South Western Ethiopia reported that only 29% of the participants were willing to receive the vaccine (19). The relatively high willingness to accept the vaccine could be attributed to the vigorous campaigns by the government of Uganda to promote COVID-19 vaccination (20).…”
Section: Discussionmentioning
confidence: 99%
“…For example, approximately 15% of individuals quarantined due to SARS epidemic in the Canadian city of Toronto showed signs of depression and post-traumatic stress disorder [ 20 ]. Economic-related mental distress has been reported to have a negative impact on COVID-19 vaccine uptake [ 21 ]. Similarly, higher prevalence of psychological effects such as fear, anxiety and depression were reported during the 2013–2016 West Africa Ebola outbreak [ 22 ].…”
Section: Introductionmentioning
confidence: 99%